Insiderinformation och nyhetskanalers rapportering om emittenter – En utredning av definitionen och hanteringen av insiderinformation i MAR - Trydegård,Melina (2021)
The EU Market Abuse Regulation, MAR, entered into force in July 2016 and is a central framework in the field of stock-market law. The regulation provides a uniform definition of the concept of inside information that has a significant role in both the application and understanding of several provisions in the regulation. These aim to create transparency in the market, as well as to combat various types of market abuse. Available information on issuers is closely linked to the pricing of financial instruments in securities markets. When news media publish or broadcast information regarding issuers, the consequence may be that the share values of the concerned issuers are being significantly affected. The purpose of this master thesis has been to investigate the definition of inside information in MAR and whether information about an upcoming publication or broadcast in news media, concerning an issuer, can be inside information. Furthermore, the purpose has been to investigate which possible provisions in MAR that can be actualized. A legal analytical method and an EU legal perspective have been used. The definition of inside information consists of four independent and cumulative conditions that must be assessed in the light of the circumstances of the individual case. MAR stipulates an obligation for issuers to disclose inside information and to draw up an insider list. Furthermore, there is a prohibition of unlawful disclosure of inside information and on insider dealing. It is not entirely clear whether information about an upcoming publication or broadcast in a news channel can be inside information – at least not when the content of it itself is not considered to be inside information. As ESMA states in the report from 2020 about MAR, it would be appropriate to clarify certain parts of the current definition in order to have a consistent interpretation established at an EU-level and to increase the predictability in the application of the law.
Keywords: associationsrätt; EU-rätt; aktiemarknadsrätt; insiderinformation; MAR; marknadsmissbruksförordningen